A spectral filament model for turbulent transport and scrape off layer width in circular geometry. (May 2019) - Fedorczak, N.; Peret, M.; Bufferand, H.; Ciraolo, G.; Ghendrih, Ph.; Tamain, P.
Highlights: Properties of particle transport in limited scrape off layer plasma are investigated. A reduced model of filamentary transport is derived predicting the SOL width in simple plasma geometry. It is validated against non linear simulations. It is validated against experimental database in circular geometry. It shows striking features with SOL width sensitivity with control parameters. Abstract: Radial transport in scrape off layer is commonly attributed to the intermittent convection of plasma filaments. These filaments are observed in experiments, and commonly reproduced by turbulent simulations. These simulations are able to reproduce both filament velocities and main scrape off layer (SOL) widths measured in circular plasma geometries. In this contribution a comprehensive model of transport is derived, predicting the absolute amplitude of radial flux and SOL widths from interchange turbulence. This spectral filament model (SF model) describes the contribution to the radial flux of an assembly of poloidal waves representing plasma filaments. A model of density and potential spectra is detailed, leading to a simple expression of the time average turbulent radial flux and SOL width. The model shows a quantitative agreement with flux-driven simulations, as well as experimental measurements over a wide range of conditions. Predictions for ITER start-up conditions also recover the extrapolations from multi-machine databases. The SF model is derived for circular plasma shapes with weak flow shear, and gives a SOL width that varies mainly with the poloidal magnetic field, weakly with the toroidal magnetic field, and weakly but positively with the plasma major radius. Interestingly, this sensitivity with main control parameters is qualitatively close to what is found for diverted conditions in both L and H mode.